(untitled) (American Journal of Youth and Women Empowerment, 2023)
Promoting women’s empowerment in agriculture is very vital since efforts towards ensuring food security have identified women farmers as key role players in many contexts and set-ups. This study aims to identify and understand the significant factors responsible for empowering women in smallholder irrigation schemes as these may play a crucial role in poverty reduction among women farmers. The authors applied a simple random technique to select 174 women from 8 irrigation schemes across Vhembe and Sekhukhune districts of South Africa. Primary data were collected on their demographics and empowerment using a modified Women Empowerment Agriculture Index developed by IFPRI. This index concludes that women are disempowered. The determinants of empowerment were estimated using multiple linear regression analysis. The results show that there wasa strong correlation between socio-economic characteristics and empowerment; however, only four out of eleven independent variables were significant (i.e., age, marital status, number of dependants and expenditure). The study provides policy suggestions to maintain and improve where women are empowered and to correct where they are disempowered.